Facile solution synthesis and characterization of porous cubic-shaped superstructure of ZnAl(2)O(4) - Zhu, Z.; Li, X.; Zhao, Q.; Liu, Shaomin; Hu, X.; Chen, G. (Elsevier BV, 2011)
Porous and cubic-shaped superstructure of ZnAl2O4 was successfully synthesized by a facile wet chemical solution-phase method. The structural properties of the samples were systematically investigated by X-ray powder diffraction (XRD), Brunauer–Emmet–Teller (BET), scanning electron microscopy (SEM), energy-dispersive spectra (EDS), and Fourier transform infrared spectroscopy (FT-IR) techniques. The characterization results revealed that the structure of the cubic-shaped ZnAl2O4 was an inverse spinel structure. The sample prepared by a solution-phase chemical method has a higher surface area and monomodal pore size distributions. Furthermore, the valence states and the surface chemical compositions of ZnAl2O4 were further identified by X-ray photoelectron spectroscopy (XPS). This study provides a simple method to prepare cubic-shaped ZnAl2O4 in large scale, which broadens their practical applications.